Comparing preferences for outcomes of psoriasis treatments among patients and dermatologists in the U.K.: results from a discrete‐choice experiment. (1st March 2017) - Gonzalez, J.M.; Johnson, F.R.; McAteer, H.; Posner, J.; Mughal, F.
Summary: Background: Plaque psoriasis can have a significant negative effect on patients' quality of life, and treatments can result in serious toxicities. Although there have been several studies of patients' and physicians' relative preferences for the benefits and risks of psoriasis treatments, it is unclear how and whether patients' and physicians' preferences for the outcomes of psoriasis treatments differ. Objectives: To quantify patient and dermatologist preferences for improvements in psoriasis symptoms and for increases in the risk of treatment‐related serious adverse events. Methods: Members of the U.K. Psoriasis Association and U.K. dermatologists with experience prescribing biologics completed a web‐enabled discrete‐choice experiment survey in which they evaluated efficacy and safety features of biological treatments for psoriasis. Choices between hypothetical treatment options were used to estimate preference weights indicating respondents' relative trade‐off preferences among treatment outcomes. These outcomes included improvements in the severity and coverage of psoriatic plaques and treatment‐related risks of tuberculosis, serious infections and lymphoma. Preference estimates were used to derive the maximum level of side‐effect risks that respondents would accept for improvements in psoriasis symptoms. Results: Respondents' tolerance for side‐effect risks varied with side‐effect severity and location of plaques, and risk tolerance for serious side‐effects was greater for patients than for dermatologists. Conclusions: Estimates of patients' risk tolerance for serious side‐effects indicate that patients valued psoriasis symptom control highly and suggest that psoriasis symptoms have a significant effect on patients' quality of life. In light of research showing increased treatment satisfaction and improved treatment adherence among patients who receive therapies that are consistent with their preferences, our findings suggest that greater communication between dermatologists and patients about risk tolerance could help improve patient care.